Stars versus warnings: Comparison of the Australasian Health Star Rating nutrition labelling system with Chilean Warning Labels - Fredrik Söderlund; Helen Eyles; Cliona Ni Mhurchu (Australian and New Zealand Journal of Public Health, 2020)
Abstract Objective: The Health Star Rating (HSR) is a voluntary front‐of‐pack nutrition labelling system that rates products from ½ to 5 stars (five being healthiest). The Chilean Warning Label system displays warnings on foods high in sugar, saturated fat, sodium, or energy. We aimed to evaluate alignment between the systems. Methods: New Zealand packaged products (n=13,868) were classified according to the two systems. Alignment was assessed by cross‐checking the number of products meeting the criteria for warnings against star ratings. Products with no warnings but an HSR <2, or with >1 warning but an HSR of ≥3.5 were considered outliers. Results: Two‐thirds of products met the criteria for at least one warning. There was a significant positive relationship between the number of warnings and mean HSR: 0 warnings = HSR 3.77±.0166 (p<0.001), 1 warning = HSR 2.70±.0206 (p<0.001) and >1 warning = HSR 2.00±.0160 (p<0.001). The systems were non‐aligned for 1,117 products (8%). Conclusion: HSR and the Chilean Warning Label systems are broadly aligned. Non‐alignment is due to the Chilean system restricting warnings to foods containing added ingredients and HSR awarding points for positive components. Implications for public health: These results could be helpful in informing improvements to the HSR system.